PERSUASIVE STRATEGIES OF SAMOSIR PROMOTION IN @1000TENDA INSTAGRAM POSTS - Andre Manik; Iskandar Zulkarnain; Linda Astuti Rangkuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This study dealt with persuasive strategies in @1000tenda Instagram Post. The objectives of this study were to describe and to find out the dominant technique and strategies of persuasive used in @1000Tenda Instagram Post. This study was conducted by applying descriptive qualitative design. The data were collected from @1000tenda Instagram Post. After the data analyzed, it was found out 6 types of persuasive techniques and 3 types of persuasive strategies used in @1000tenda Instagram Post. The most dominant persuasive techniques used was suggestion and the most dominant persuasive strategies used was phatos.